Just Running Away: The English Literature’s Perceptions of Being a Global Worker - Alamsyah, Aam; Santosa, Santosa; Mutaat, Mutaat; Try Gustary, Devian; Cheda Asniati, Andina (Jurnal Pendidikan Bahasa, 2025)
Amid Indonesia's vulnerable economic situation, the idea of finding jobs overseas has evoked numerous responses. The present study scrutinized the English literature students’ perceptions regarding potential migration abroad, the countries where they want to work, and the language they need. The study was driven by the hypothesis that English language skill might be needed more abroad than in the Indonesian context. Up to this time, the government has strived to solve Indonesian unemployment, which continuously increases annually. Finding a job overseas can be an alternative to alleviating the government's economic burden and reducing the number of unemployed in Indonesia simultaneously. The present study employed a mixed method involving seventy-five English literature students. The participants were recruited conveniently from the English classes where the researchers teach. The instrument used was a written questionnaire followed by interviews with selected participants. The findings indicated that the participants had more ideas about visiting Asian countries. Furthermore, Europe, Arabia, Canada, and North America are the following countries that have the most potential to visit. The participants were also convinced that using English in Asian countries would be helpful, even though other Asian languages might be more suitable for use in the Asian continent than English. Other languages that the participants perceived essential to learn are Mandarin, Japanese, Arabic, Korean, and German. The study highlights the potential migration among educated Indonesians (i.e., English literature/English students), which would incur multiple benefits if substantial changes were enacted by authority.